Effect of Rice Milling on Their Polyphenol, Protein Content and Antioxidant Activity - Soyema Khatun; Md. Mahi Imam Mollah (International Journal of Agricultural Sciences, 2021)
The phenolic compound is the main source of antioxidants that reduces the incidence of chronic diseases such as heart disease, blood cholesterol, blood pressure, diabetes, etc. This experiment aimed to investigate the effect of the three milling processes of rice (dehusking, auto, and polishing) on polyphenol content with their antioxidant activity and nutritional profile. The polyphenol content was determined according to the Folin Ciocalteu method. Polishing rice contained a maximum phenolic compound (36.28 ± 0.73mg/g of extract) that was statistically different from other milling rice (p<0.05). Polishing rice contained the highest amount of protein (262.69 ± 0.38mg/g extract), whereas auto rice contained the highest amount of free amino acid content (14.06 ± 0.46mg/g extract) and total sugar content (1312.29 ± 2.28mg/g extract). Reducing sugar content was statistically similar to all milling rice. Antioxidant activity was comparatively assessed by ABTS (2, 2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid) free radical decolorization assay method. It was investigated that polishing rice showed strong free radical scavenging capacity by ABTS radical. It is concluded that polishing rice can be used as a functional ingredient with high polyphenol and protein content with strong antioxidant activity.